2016
DOI: 10.1128/aem.03420-15
|View full text |Cite
|
Sign up to set email alerts
|

The Exiguobacteriumsibiricum 255-15 GtfC Enzyme Represents a Novel Glycoside Hydrolase 70 Subfamily of 4,6-α-Glucanotransferase Enzymes

Abstract: The glycoside hydrolase 70 (GH70) family originally was established for glucansucrase enzymes found solely in lactic acid bacteria synthesizing ␣-glucan polysaccharides from sucrose (e.g., GtfA). In recent years, we have characterized GtfB and related Lactobacillus enzymes as 4,6-␣-glucanotransferase enzymes. These GtfB-type enzymes constitute the first GH70 subfamily of enzymes that are unable to act on sucrose as a substrate but are active with maltodextrins and starch, cleave ␣1¡4 linkages, and synthesize l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
105
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 42 publications
(116 citation statements)
references
References 33 publications
3
105
1
Order By: Relevance
“…In recent years several maltodextrins/starch converting enzymes have been identified within the GH70 family supporting the evolutionary relatedness of GH13 and GH70 families23242526. Firstly, it was found that L. reuteri 121 produced a GS-like enzyme that was inactive on sucrose.…”
mentioning
confidence: 80%
See 4 more Smart Citations
“…In recent years several maltodextrins/starch converting enzymes have been identified within the GH70 family supporting the evolutionary relatedness of GH13 and GH70 families23242526. Firstly, it was found that L. reuteri 121 produced a GS-like enzyme that was inactive on sucrose.…”
mentioning
confidence: 80%
“…Besides, GSs present a “U-fold” domain structure in which 4 (domains A, B, IV and V) of the 5 domains are built up from two discontinuous segments of the polypeptide chain122021. During their evolution from GH13, the GH70 enzymes appear to have undergone a sequence of gene rearrangements that resulted in this unusual, circularly permuted domain organization23.…”
mentioning
confidence: 99%
See 3 more Smart Citations